The Effect of Stretching and Ergonomic Sitting Posture on Low Back Pain (LBP) in Workers - Syna Yusterien Martatias; Diyanah Syolihan Rinjani Putri; Saelan Saelan (GLOBAL HEALTH SCIENCE GROUP, 2025)
LBP is the main cause of decreasing work productivity and work absence in most of the big countries in the world. Office employees generally use computers for a long duration with incorrect or non-ergonomic sitting posture. Incorrect or non-ergonomic sitting posture and long sitting duration increase the risk of LBP. Efforts that can be made to control LBP are stretching and ergonomic sitting posture. Objective: the aim of this study is to determine the effect of stretching and ergonomic sitting posture on Low Back Pain (LBP) in workers at PT ADMEDIKA Surakarta. Method: This study used an observational analytical design with a cross-sectional approach. Sampling used a total sampling technique. There were 52 workers who experienced LBP. This study was conducted in PT Admedika Surakarta from Apri 24 to May 26, 2024. The instrument used the Numeric Rating Scale (NRS) questionnaire. The intervention of stretching and ergonomic sitting posture was 2-3 minutes long for 2 rounds and carried out 3 times per week. The data analysis used a parametric test in the form of a Paired T-test. Results: The results of data analysis obtained a significance value of 0.000 < 0.05. Conclusions: which can be concluded that there is an effect of stretching and ergonomic sitting posture on Low Back Pain (LBP) in workers of PT ADMEDIKA Surakarta.